ARANG AKTIF KULIT PISANG KEPOK DALAM MENGIKAT LOGAM BERAT TIMBAL - Dewi Patracia; Anita Dewi Moelyaningrum; Rahayu Sri Pujiati (Jurnal Berkala Kesehatan, 2019)
Landfill activity can pollute the surrounding environment. Heavy metals are contaminants that are harmful to the environment. Musa Paradise Linn sppeel from Jember District, Indonesia contains 55% cellulose which allows it to adsorb Pb heavy metals. The purpose of this study is to analyze the differences in Pb levels in the untreated group of mass addition of Musa paradise Linn sppeel activated charcoal 0g/200ml (P0), with well water treated with mass addition of banana peel activated charcoal 2g/200ml (P1), 3g/200ml (P2), and 4g/200ml (P3) with well water containing Pb for 10 minutes. This study is a True Experiment with and uses the Complete Random Design (CRD) method with six repetitions.Each sample was contacted with Pb water stirred using a magnetic stirrer at 300 rpm for 10 minutes, then filtering using filter paper to separate the charcoal from the water. Data were analyzed using Kolmogorov Smirnov then ANOVA One Way. The results showed that there were differences in the decrease in Pb levels that were significant between the control group (P0), and the groups treated for the addition of Musa Paradise Linn sppeel activated charcoal (P1 = 0,000; P2 = 0,000; P3 = 0,000). The Musa paradise Linn sp peel activated charcoal significant to adsorb the lead (Pb) in the water.